Application of new world camelidae microsatellite primers for amplification of polymorphic loci in old world camelids - Han Jianlin; Mburu, D.; Ochieng, J.; Kaufmann, J.B.; Rege, O.; Hanotte, Olivier H. (Wiley, 2000)
Twenty new world camelidae primer pairs were selected for cross-species amplification of loci in the old world camelids, the dromedary (Camelus dromedarius) and the bacterian (camelus bactrianus). A panel of DNA samples from 34 unrelated dromedaries (Kenya) and from 34 unrelated bactrians (32 domestic bactrians and two wild bactrians, China) were amplified. DNA samples from two llamas (Lama glama) and two alpacas (Lama pacos) were used as positive controls. PCR conditions; amplification and polymorphism, and microsatellite sequences were assessed and results presented.